Pengaruh Lingkungan Kerja, Asistensi Manajemen, dan Kebijakan Kompensasi Terhadap Retensi Karyawan di SMK Hang Tuah 2 Jakarta - Wullur , Susana; Wahyudin , Dian (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This research aims to analyze the influence of the work environment, management assistance, and compensation policy on employee retention at SMK Hang Tuah 2 Jakarta. Data was collected using a questionnaire that was tested for validity and reliability. The research sample consisted of 50 employees of SMK Hang Tuah 2 Jakarta, selected using a saturated sampling technique. The data analysis technique employed multiple linear regression analysis using SPSS for Windows Ver. 29. The findings of this research indicate that: (1) the work environment has a positive and significant influence of 65.8% on employee retention variation, with a significance value of 0.001, (2) management assistance has a positive and significant influence of 74.1% on employee retention variation, with a significance value of 0.006, (3) compensation policy has a positive and significant influence of 85.1% on employee retention variation, with a significance value of 0.000, and (4) simultaneously, the work environment, management assistance, and compensation policy have a positive and significant influence of 85.5% on employee retention variation, with a significance value of 0.000. These findings indicate that improving the work environment, management assistance, and compensation policy will enhance employee retention.